2020
DOI: 10.3174/ajnr.a6655
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Complications in COVID-19 Infection: Case Series

Abstract: We present a series of 10 hospitalized patients with confirmed coronavirus 2019 infections who developed severe neurovascular complications and discuss the possible reasons for these findings and their relationship to the novel Severe Acute Respiratory Syndrome coronavirus 2 infection. ABBREVIATIONS: ACE2 ¼ angiotensin-converting enzyme 2; COVID-19 ¼ coronavirus 2019; CRP ¼ C-reactive protein; CSS ¼ cytokine storm syndrome; ICU ¼ intensive care unit; LDH ¼ lactate dehydrogenase; PCR ¼ polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Ischemic Stroke 37 Articles [39], [57], [58], [60], [63], [73], [74], [75], [76] [77], [78], [79], [80],. [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [178], [192] 363 NR in all articles.…”
Section: Cerebrovascular Eventsmentioning
confidence: 96%
See 1 more Smart Citation
“…Ischemic Stroke 37 Articles [39], [57], [58], [60], [63], [73], [74], [75], [76] [77], [78], [79], [80],. [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [178], [192] 363 NR in all articles.…”
Section: Cerebrovascular Eventsmentioning
confidence: 96%
“…19 Articles [39], [57], [58], [60], [63], [75] [86]), [92], [98], [99], [100], [101], [106], [107], [108], [109], [110], [111], [112 [101], [102], [114], [115], [116], [117], [118], [192] Dixon L et al [149] reported ANE in a 59 Y/O F with history of aplastic anemia who died despite steroid therapy.…”
mentioning
confidence: 99%
“…Acute intracranial bleeding was reported in 35 patients with COVID-19 in the literature ( Table 2, Supplementary Table 2): 24 patients (68.57%) had intracerebral hemorrhage (ICH), 4 patients (11.43%) had non-traumatic subarachnoid hemorrhage (SAH), and the remaining 7 patients (20%) had the simultaneous presence of SAH and ICH. The mean age of the 35 patients with intracranial bleedings was 59.89 ± 11.91 years and 67.4% were males (16,25,28,64,71,73,(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121). Two of the 11 patients with non-traumatic SAH (regardless of the presence of ICH) were found to have a ruptured dissecting aneurysm (one in the posterior inferior cerebellar artery; one in the pericallosal artery).…”
Section: Intracranial Bleedingmentioning
confidence: 99%
“…It is not yet known whether this knowledge applies to the new SARS-CoV-2. So I n P r e s s far, several imaging findings have been described in the setting of COVID-19, but the relationship with SARS-CoV-2 remains unclear (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%